2019
DOI: 10.1186/s13068-019-1416-9
|View full text |Cite
|
Sign up to set email alerts
|

Expression and secretion of a lytic polysaccharide monooxygenase by a fast-growing cyanobacterium

Abstract: Background Cyanobacteria have the potential to become next-generation cell factories due to their ability to use CO 2 , light and inorganic nutrients to produce a range of biomolecules of commercial interest. Synechococcus elongatus UTEX 2973, in particular, is a fast-growing, genetically tractable, cyanobacterium that has garnered attention as a potential biotechnological chassis. To establish this unique strain as a host for heterologous prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…cDNA encoding the AA10 modules, including the native SEC secretion signal peptide, of Cfi LPMO10, Cfla LPMO10A, Cfla LPMO10B, and Cfla LPMO10C, was cloned from genomic DNA with the addition of a C-terminal His 6 purification tag and transformed into E. coli for expression. Secretion of LPMO proteins through the SEC pathway in E. coli has previously resulted in accumulation of recombinant protein in the periplasm [ 91 , 92 ] and the culture medium [ 93 , 94 ], with the former necessitating periplasmic fractionation. We observed that the majority of the recombinant Cellulomonas LPMOs were found in the media, with negligible amounts in the periplasm.…”
Section: Resultsmentioning
confidence: 99%
“…cDNA encoding the AA10 modules, including the native SEC secretion signal peptide, of Cfi LPMO10, Cfla LPMO10A, Cfla LPMO10B, and Cfla LPMO10C, was cloned from genomic DNA with the addition of a C-terminal His 6 purification tag and transformed into E. coli for expression. Secretion of LPMO proteins through the SEC pathway in E. coli has previously resulted in accumulation of recombinant protein in the periplasm [ 91 , 92 ] and the culture medium [ 93 , 94 ], with the former necessitating periplasmic fractionation. We observed that the majority of the recombinant Cellulomonas LPMOs were found in the media, with negligible amounts in the periplasm.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial LPMOs are usually overexpressed in the periplasm of Escherichia coli [33,45,49]. However, other strategies for AA10 LPMO production in the cytoplasm of E. coli with a cleavable N-terminal tag [17,19,20] or as secreted protein using Gram-positive bacteria (Brevibacillus choshinensis SP3 or Bacillus subtilis) [18,50], cyanobacteria (Synechococcus elongatus UTEX 2973) [51], or yeast (Pichia pastoris) [52] as expression host have also been successfully developed. Using E. coli as recombinant expression system, we chose the N-terminal pelB signal peptide to direct PlAA10 production to the periplasm.…”
Section: Plaa10 Binds Copper Similarly To Other Chitin-active Lpmosmentioning
confidence: 99%
“…In our previous study, we demonstrated the secretion of the LPMO TfAA10A from T. fusca in the cyanobacterium S. elongatus UTEX 2973 (24). TfAA10A is a copper-containing enzyme with a complex catalytic cycle not suitable for high-throughput analysis.…”
Section: Nluc Is Efficiently Secreted In Synechocystis Sp Pcc 6803mentioning
confidence: 99%
“…Previously we have shown that the fast-growing cyanobacterium Synechococcus elongatus UTEX 2973 can secrete the heterologously expressed enzyme TfAA10A, a lytic polysaccharide monooxygenase (LPMO) from the gram-positive bacterium Thermobifida fusca. TfAA10A was secreted via a two-step process with the cleavage of its N-terminal Sec signal peptide occurring when crossing the cytoplasmic membrane (24). To address whether the T4aPS can secrete non-pilin proteins, we developed a NanoLuc luciferase (NLuc)-based secretion reporter harboring the TfAA10A signal peptide and genetically transferred the reporter into a collection of cyanobacterial T4aPS mutants.…”
Section: Introductionmentioning
confidence: 99%